2017
DOI: 10.1159/000479480
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Kidney Transplantation for African Americans

Abstract: Background: The persistent challenges of bridging healthcare disparities for African Americans (AAs) in need of kidney transplantation continue to be unresolved at the national level. This healthcare disparity is multifactorial: stemming from limited kidney donors suitable for AAs; inconsistent care coordination and suboptimal risk factor control; social determinants, low socioeconomic status, reduced access to care; and mistrust of clinicians and the healthcare system. Summary: There are numerous opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 65 publications
2
73
0
Order By: Relevance
“…Our study also suggests that among those who are listed, SES and comorbidity may have less influence on receipt of transplant. This is consistent with work that suggests immunologic concerns and availability of donor organs are important predictors for transplant (2,17). Prior national policies have focused on allocation stage of organ transplantation (32,33), yet disparities in transplantation may be widening between 1995 and 2014 (3) and within donor evaluation process (34).…”
Section: Discussionsupporting
confidence: 80%
“…Our study also suggests that among those who are listed, SES and comorbidity may have less influence on receipt of transplant. This is consistent with work that suggests immunologic concerns and availability of donor organs are important predictors for transplant (2,17). Prior national policies have focused on allocation stage of organ transplantation (32,33), yet disparities in transplantation may be widening between 1995 and 2014 (3) and within donor evaluation process (34).…”
Section: Discussionsupporting
confidence: 80%
“…Qualitative evidence highlighted several barriers for KTx among the Indigenous Americans including mistrust of the safety of the deceased organ, ethical concerns about the procurement process, fear of surgery, and concerns about maintaining the body whole to maintain spiritual balance [ 26 29 ]. Similar barriers were identified among Black Americans including mistrust of the medical team, fear of surgery, care coordination barriers and other cultural factors (such as perceived discrimination) [ 25 , 30 32 ]. Like the Indigenous Americans, the disparity in KTx access for Black Americans cannot be fully explained by medical or socioeconomic variables [ 3 ].…”
Section: Discussionmentioning
confidence: 79%
“…Optimizing care coordination between government funded tribal health services and specialty care such as transplant has been an ongoing quality effort [ 24 ]. The effect of lack of care coordination has been associated with disparity in KTx access for Black Americans [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing data have shown that minoritized groups such as African American and Hispanics are referred later for transplantation in their ESKD course. Proposed contributors include patient preferences, clinician biases, poor patient education, low socioeconomic status, more frequent contraindications to transplantation, inadequate health insurance, and immunologic factors [21]. Although the intervention clinic nephrology care was primarily delivered by fellows, the intervention could be applied to attending nephrology clinics and community clinics regardless of academic affiliation.…”
Section: Discussionmentioning
confidence: 99%